2003
DOI: 10.1057/palgrave.cpcs.8140143
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of Street Lighting, Crime and Fear of Crime in the British City

Abstract: The UK government has recently made £300 million available to help local authorities to modernise their street lighting. In consideration of such future funding, this paper reviews the relationship between lighting and crime, explores the current theoretical explanations, and discusses the limitations of the existing BS 5489 lighting standards as they relate to crime reduction.British street lighting standards rely largely on official recorded crime statistics as the preferred measure of crime and, crucially, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…A follow-up study of lighting at Valley Lines railway stations is currently underway with the objective of investigating lighting standards and existing lighting levels at railway stations in an attempt to allay such widespread and specific personal safety fears. Indeed, a recent study has revealed that current street lighting levels may not always be met, and indeed, the standards may themselves require refinement (Cozens et al, 2003). Although at an early stage, as part of its commitment to improve passenger safety, Valley Lines have installed transparent shelters at seven stations in order to evaluate the perceived effectiveness of this design modification.…”
Section: Resultsmentioning
confidence: 99%
“…A follow-up study of lighting at Valley Lines railway stations is currently underway with the objective of investigating lighting standards and existing lighting levels at railway stations in an attempt to allay such widespread and specific personal safety fears. Indeed, a recent study has revealed that current street lighting levels may not always be met, and indeed, the standards may themselves require refinement (Cozens et al, 2003). Although at an early stage, as part of its commitment to improve passenger safety, Valley Lines have installed transparent shelters at seven stations in order to evaluate the perceived effectiveness of this design modification.…”
Section: Resultsmentioning
confidence: 99%
“….deterrent effects of good design, layout and lighting'. 8 Wayfinding studies use the term reassurance when discussing the use of signage and landmarks to confirm that the correct route is being followed. 9,10 A place will be considered unsafe (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between lighting intensity and crime can therefore be determined as situational, as it can only be determined through specific cases and cannot be applied as a general rule of thumb. However, higher street light luminance usually reduces fear of crime, especially in women [80,81]. Table 1 shows relevant published studies on the effect of lighting on crime where the uncertainty described above is obvious.…”
Section: City Lighting and Crimementioning
confidence: 99%